Linking green entrepreneurial orientation and ambidextrous green innovation to stimulate green performance: a moderated mediation approach - Baquero, Asier (Business Process Management Journal, 2024)
Purpose: In view of the significance of intangible organizational resources and firm sustainability, this study investigates the mediating role of ambidextrous green innovation and the moderating effects of resource orchestration capability in the relationship between green entrepreneurial orientation and green performance. Design/methodology/approach: The research employed a quantitative analysis technique using hierarchical linear regression and a moderated mediation approach on a sample of 409 managers from UAE manufacturing firms to investigate the proposed relationships among the variables. Findings: The research results show that a firm’s green performance is influenced by its green entrepreneurial orientation. Green innovation, both exploratory and exploitative, mediates the link between green entrepreneurial orientation and green performance. Moreover, the association between green entrepreneurial orientation and exploitative green innovation, as well as between exploitative green innovation and a firm's green performance, is strengthened by resource orchestration capability. The findings of the moderated mediation show that when resource orchestration capacity is high, exploitative green innovation has a greater mediating effect on green entrepreneurial orientation and green performance. Practical implications: This study provides valuable insights for manufacturing firms to achieve sustainable performance and reduce their environmental impact. Firms should adopt proactive environmental strategies and innovative approaches to achieve sustainable green performance by adopting green entrepreneurship and establishing ambidextrous green innovation. Originality/value: This study contributes to the literature on GEO, ambidextrous green innovation, resource orchestration capability, and green performance. These results provide insight into fostering green innovation in the manufacturing industry, deepen the theoretical foundation for green entrepreneurship, and advance the field of green entrepreneurship study.
Keywords: green entrepreneurial orientation; exploitative green innovation; exploratory green innovation; green performance; resource orchestration capability